Métodos de plantación forestal para el manejo de especies provenientes de la regeneración natural en comunidades de la quebrada Chiriyacu, Nauta – Loreto - Portocarrero Silva, Pedro (2007)
The present study was carried out in the secondary forests of the rural communities of Santa Fe, Villa Buen Pastor and Villa Cristiana, located en the left bank of the Marañon river, jurisdiccion of the Nauta district, Loreto province, Loreto region. The objectives of the study were: (i) to evaluate the mortality and (ii) to evaluate the phytosanitary status of the forest plantations established by direct end indirect methods with natural regeneration seedlings of four forest species in the three communities. The percentage of seedlings establishment in the definitive field plantation was from 93,1% to 93,5% when using the indirect planting method with a nursery, while by the direct method without a nursery it was from 84,2% to 87,7%, which demonstrates the advantage of using the acclimatization nursery before installing the seedlings in the definitive field plantation. Marupá is the species with the highest seedling establishment when using the indirect planting method with a nursery with 96%, followed by tornillo, moena and cumala with 94%, 93% and 91%, respectively; by using the method of direct planting without nursery marupá is again the species with the highest seedling establishment with 88%, followed by tornillo, moena and cumala with 87%, 85% and 83%, respectively. The absence of leaflets in the seedlings was the greatest damage observed in the definitive field plantation, with cumala being the most affected and, occasionally, tornillo and marupá; the occurrence of withered leaves was also observed in tornillo and moena. It is recommended to replicate the experience of this study in other forest species of ecological and economic importance.